Footwear Toe‐Box Shape and Medial Forefoot Pressures in Women With Hallux Valgus - Katrina J. Bajraszewski; Polly Q. X. Lim; Andrew K. Buldt; Sheree E. Hurn; Karen J. Mickle; Edward Roddy; Anita E. Wluka; Bircan Erbas; Shannon E. Munteanu; Hylton B. Menz (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background Narrow fitting footwear is a modifiable risk factor for the development of hallux valgus (HV). Despite this, the pressure that footwear exerts at the medial forefoot has not been fully evaluated in people with HV. Therefore, the objective of this study was to determine whether the toe box of footwear habitually worn by women with HV is associated with pressure exerted on the medial forefoot. Methods In‐shoe peak pressure and maximum force at the medial forefoot (distal and proximal sites) were recorded from 28 women (mean age 60.7 years, SD 10.7) with moderate or severe HV using the pedar pad pressure system (Novel GmbH, Germany). The shape (width and area) of the participants' most symptomatic foot and toe‐box of their usual footwear was determined using an INFOOT 3D laser scanner (I‐Ware Laboratory, Japan) and hand tracing, respectively. The difference between the foot and corresponding footwear measurements as well as differences in the magnitude and timing of peak pressure and maximum force between the proximal and distal forefoot were determined using independent t‐tests. Correlations between forefoot pressures with toe‐box differential were determined using Spearman's ρ analyses. Results Peak pressure and maximum force were significantly greater (mean difference [MD] = 33.0 ± 15.4 kPa; p < 0.001 and 12.8 ± 7.3 N; p = 0.001) and occurred slightly later in the stance phase at the distal forefoot compared to the proximal forefoot (MD = 6.0 ± 6.9%; p = 0.083 and 6.9 ± 6.8%; p = 0.045, respectively). There were no significant correlations between toe‐box differential and medial forefoot pressures, with all correlations less than 0.35 (p > 0.05). Conclusion Toe‐box shape and fit of footwear typically worn by older women with painful HV was not associated with increased medial forefoot pressures in this study sample. Therefore, changing the toe‐box width and area of the usual footwear worn by older women with painful, moderate or severe HV may not necessarily reduce medial forefoot pressures where footwear does not appear to play a role.